Pengaruh Brand Ambasador, Electronic Word oF Mouth, dan Gaya Hidup terhadap Keputusan Pembelian Skincare Somethinc di Kota Yogyakarta - Lintang Sukma Ningrum; Ambar Lukitaningsih; Diansepti Maharani, Bernadetta (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to test whether Brand Ambassador, Electronic Word Of Mouth, and Lifestyle have an influence on Purchase Decisions for Somethinc skincare in Yogyakarta City. This research took samples from consumers who purchased and used some type of skincare, aged 18 to 25 years, female and male, as well as students who live in the city of Yogyakarta. The method used uses a non-probability sampling technique with a purposive sampling method. Data collection was carried out by distributing questionnaires which were distributed online using Google Form. The number of respondents' data processed was 112 people which was obtained using the Hair formula, namely the number of indicators multiplied by 7. This research data was analyzed using multiple linear analysis and this processing was carried out using SPSS version 20. The results of this research show that the variables Brand Ambassador (X1), Electronic Word of Mouth (X2) and Lifestyle (X3) partially and simultaneously influence the Purchasing Decision variable (Y)